Ultrahigh-temperature-resistant lightweight nano-microporous insulation board and preparation method thereof

By combining nanoscale fumed silica, alumina, and micron-scale light-blocking agents with reinforcing fibers, an ultra-high temperature resistant lightweight nanoporous insulation board was prepared, which solved the contradiction between lightweight and temperature resistance at high temperatures, and achieved high efficiency insulation performance and structural stability, making it suitable for high-precision manufacturing.

CN120965269APending Publication Date: 2025-11-18NANTONG ECOTHERM INSULATIONS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511063082.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing thermal insulation materials struggle to balance lightweight and temperature resistance in high-temperature environments, and suffer from high thermal conductivity, poor dimensional stability, and insufficient process controllability. In particular, new thermal insulation materials with ultra-low thermal conductivity, ultra-high dimensional stability, and lightweight are urgently needed in high-precision manufacturing fields such as aerospace thermal protection and new energy battery insulation.

Method used

By combining nanoscale fumed silica, nanoscale fumed alumina, micron-level light-blocking agent, and reinforcing fibers, and through specific stirring and pressing processes, a synergistic effect is formed to suppress high-temperature convective heat transfer, reflect infrared radiation, and maintain structural integrity, thus preparing an ultra-high temperature resistant lightweight nanoporous insulation board.

Benefits of technology

With a density of 240-290 kg/m³, it achieves a thermal conductivity of ≤0.030 W/m·K at 1000℃, a linear shrinkage rate of ≤2.0%, a fiber breakage rate of <0.5%, and a density deviation of <5%, meeting the insulation requirements of high-temperature and high-precision manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120965269A_ABST
    Figure CN120965269A_ABST
Patent Text Reader

Abstract

The invention relates to an ultrahigh temperature-resistant light nano-microporous heat insulation plate and a preparation method thereof.The heat insulation plate is composed of 60-90% of nanoscale fumed silica with the particle size of 5-100 nm, 0-25% of fumed alumina, 10-35% of a micron opacifying agent with the particle size of 1.5-6.0 microns and 2-10% of reinforced fibers with the diameter of 4-15 microns, and the heat insulation plate is achieved through the synergistic effect that 1, convective heat transfer of gas at the temperature of 1000 DEG C is inhibited; 2) reflecting infrared radiation heat; and 3) maintaining the integrity of the fiber structure. The preparation method comprises the following steps: sequentially feeding and stirring aluminum oxide, silicon dioxide and the opacifying agent step by step; adding fibers for dispersion; three layers of functional paddles (a radial dispersion layer / a hinge mixed fiber layer / an anchor type anti-deposition layer) are adopted for low-speed stirring; and slowly pressing and forming. The invention has the following beneficial effects: under the density of 240-290 kg / m, the heat conductivity coefficient at 1000 DEG C is less than or equal to 0.038 W / m.K, the linear shrinkage rate is less than or equal to 2.0%, the fiber fracture rate is less than 0.5%, and the technical contradiction between light weight and ultrahigh temperature resistance is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of insulation board production technology, and in particular to an ultra-high temperature resistant lightweight nanoporous insulation board and its preparation method. Background Technology

[0002] In fields such as high-temperature industrial equipment and aerospace, high-efficiency thermal insulation materials are crucial for energy conservation and safety. Currently, mainstream thermal insulation materials exhibit significant drawbacks in extreme temperature environments (≥1000℃):

[0003] While traditional ceramic fiberboard has temperature resistance, its density usually exceeds 300 kg / m³, which leads to excessive equipment load. Furthermore, its thermal conductivity rises sharply to over 0.05 W / m·K at high temperatures, and its linear shrinkage rate exceeds 3%, which can easily cause structural cracking and failure with long-term use.

[0004] Although calcium silicate-based thermal insulation materials achieve lightweight (density of about 220 kg / m³), they are brittle, have poor thermal shock resistance, and can withstand temperatures of no more than 800°C, which cannot meet the needs of high-temperature kilns and other similar applications.

[0005] Aerogel composites have ultra-low thermal conductivity (≤0.020W / m·K) at room temperature, but the nanoporous structure is prone to collapse at high temperatures. The thermal conductivity deteriorates to more than 0.060W / m·K at 1000℃, and the insufficient mechanical strength makes it difficult to apply on a large scale.

[0006] The industry's technological bottlenecks are mainly manifested in the following ways:

[0007] The contradiction between lightweight and temperature resistance: materials with a density ≤290kg / m³ are difficult to maintain a thermal conductivity ≤0.040W / m·K at 1000℃;

[0008] Insufficient dimensional stability: High-temperature thermal stress causes shrinkage exceeding 2.5%, accelerating material aging;

[0009] Poor process controllability: Nanoparticles are prone to agglomeration or breakage during the mixing process with fibers, affecting the uniformity of the insulation structure.

[0010] Especially in the field of high-precision manufacturing (such as aerospace thermal protection and new energy battery thermal insulation), there is an urgent need for a new type of thermal insulation material that combines ultra-low high temperature thermal conductivity (1000℃≤0.038W / m·K), ultra-high dimensional stability (linear shrinkage rate≤2.0%), and lightweight (density 240-290kg / m³), but the existing technology system has not yet broken through these three performance barriers. Summary of the Invention

[0012] To overcome the above-mentioned defects of the prior art, embodiments of the present invention provide an ultra-high temperature resistant lightweight nanoporous insulation board and its preparation method.

[0013] To achieve the above objectives, the innovative aspects of this invention are as follows: it is composed of the following components:

[0014] Nanoscale fumed silica: particle size 5–100 nm, mass percentage 60%–90%;

[0015] Nanoscale fumed alumina: particle size 10–300 nm, mass percentage 0%–25%;

[0016] Micron-sized opacifiers: silicon carbide powder and / or zirconium silicate powder, with a median particle size D50 of 1.5–6.0 μm and a mass percentage of 10%–35%;

[0017] Reinforcing fibers: 4–15 μm in diameter, 2%–10% by mass;

[0018] The components achieve the following functions through synergistic effects:

[0019] Suppressing convective heat transfer in ambient air at 1000℃ and normal pressure;

[0020] Reflects 2–5 μm infrared radiation heat;

[0021] Maintain the integrity of the fiber structure during the pressing process;

[0022] Synergistic effects are achieved through the following technical solutions:

[0023] The particle size of fumed silica is smaller than the mean free path of gas molecules in air at 1000°C under normal pressure.

[0024] The particle size of the opaque agent is 0.3–1.2 times the infrared wavelength;

[0025] The diameter of the reinforcing fiber satisfies: ;in To enhance fiber diameter, the unit is μm. Fumed silica has a compressive strength of 50–100 MPa. To enhance the tensile strength of the fiber to 1000–2000 MPa, The average particle size of the fumed silica is 20–200 nm.

[0026] Furthermore, the ratio of the particle size of the aforementioned opaque agent to the infrared wavelength is 0.5–0.8 times.

[0027] Furthermore, in the relationship for reinforcing fiber diameter, Take 80MPa, Take 1500MPa, Taking 50nm, the calculation is as follows .

[0028] Furthermore, the aforementioned fumed silica consists of amorphous nanoparticles.

[0029] Furthermore, the surface of the insulation board is covered with a vacuum aluminum foil layer, and the composition meets the following requirements: 65%–75% by mass of fumed silica, 8%–12% by mass of fumed alumina, 13%–18% by mass of light-blocking agent, and 5%–10% by mass of reinforcing fiber.

[0030] This invention provides a method for preparing an insulation board, specifically including the following steps:

[0031] S1. Add and stir the materials in the following order: fumed alumina → fumed silica → opaque agent, with an interval of 2–7 minutes between additions.

[0032] S2. Add reinforcing fiber and continue stirring for 5–20 minutes;

[0033] S3. Fill the mixture into the mold and press it into shape using a 50–400 ton hydraulic press at a pressing speed of 3–30 mm / s.

[0034] Furthermore, the stirring in steps S1 to S2 above employs a combined impeller, comprising:

[0035] Upper dispersible layer: radially arranged flat paddles used to break up nano-agglomerates;

[0036] Middle blended layer: Folded paddles with an inclination angle of 30°–60° are used to gently blend in reinforcing fibers;

[0037] Bottom anti-deposition layer: anchor or frame paddle, used to eliminate dead zone deposition;

[0038] The blade diameter is 20–50 cm, the surface is covered with a silicone layer, the rotation speed is 300–800 rpm and the tip linear velocity is ≤10 m / s.

[0039] Furthermore, the pitch angle of the blade in the aforementioned middle fiber-blended layer is 45±5°, and the spacing between adjacent blade layers is 0.6–1.0 times the blade diameter.

[0040] Furthermore, the above-mentioned pressing process employs a purely physical exhaust process.

[0041] Further, the material is reshaped after pressing and molding.

[0042] The beneficial effects of this invention are:

[0043] 1. Achieving a synergistic breakthrough in lightweighting and ultra-high temperature resistance: Through the synergistic use of 5–100nm fumed silica (to suppress gas convection heat transfer) and 1.5–6.0μm light-blocking agent (reflecting >90% of infrared radiation), at a density of 240–290kg / m³, the following are achieved: thermal conductivity ≤0.030W / m·K at 1000℃ (0.025 in Example 1), which is more than 40% lower than that of traditional ceramic fiberboard (≥0.050); linear shrinkage rate ≤2.0% at 1000℃ (1.8% in Example 2), and high-temperature dimensional stability improved by 50%.

[0044] 2. Ensure the process controllability of lightweight structure: Based on three-layer functional stirring blades (radial dispersion layer + folded fiber mixing layer + anchor anti-deposition layer) and slow pressing process (3–30 mm / s), the following are achieved: fiber breakage rate <0.5% (0.3% in Example 1), which is 94% lower than the traditional process (>8%); density deviation <5% (±0.1 mm flatness in Example 4), ensuring the uniformity of performance of lightweight insulation board. Attached Figure Description

[0046] Figure 1 This is a side view of the blade structure of the present invention.

[0047] Figure 2 This is a flow chart of the distributed feeding process of the present invention.

[0048] Figure 3 This is a comparison chart of the performance parameters of the present invention and conventional materials. Detailed Implementation

[0050] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0051] The following embodiments detail the technical solution of the present invention. All tests in the embodiments are based on national standards:

[0052] Thermal conductivity: ASTM C177; Linear shrinkage: GB / T17911-2018; Compressive strength: GB / T1964-1996; Fiber strength: GB / T3916-2013.

[0053] Example 1: Raw materials and proportions.

[0054] Vaporized SiO2: Hoshine Silicon Industry HS-200, particle size 20nm, amorphous, 72%;

[0055] Vaporized Al2O3: Huifu Nano Aluna-100, particle size 50nm, 10%;

[0056] Light-blocking agent: Jinmeng New Materials Silicon Carbide GCW2.8, D50=2.8μm, 15%;

[0057] Reinforcing fiber: 3M Nextel ceramic fiber, 9μm in diameter, tensile strength 1500MPa, 3%.

[0058] Preparation process:

[0059] Distributed feeding, such as Figure 2 As shown: First add Al2O3 and stir for 2 min; add SiO2 after a 3 min interval and stir for 5 min; add carbonization material after a 5 min interval.

[0060] Add reinforcing fiber: Add reinforcing fiber and stir for 15 minutes (500 rpm).

[0061] Stirring blade 1: Blade spacing 25cm (0.83 times blade diameter), linear velocity 7.8m / s.

[0062] like Figure 1 As shown, the three-layer composite blade 1: upper layer dispersion: 11: 6 radial flat blades, middle layer fiber-mixed layer 12: 4 45° folding blades (pitch angle 45°), lower layer anti-deposition layer 13: 2 anchor blades; blade diameter 30cm, silicone coating thickness 4mm.

[0063] Pressing process: 200-ton hydraulic press, pressing speed 10mm / s; pure physical venting; vacuum aluminum foil wrapping after shaping.

[0064] Performance and Validation:

[0065] Synergistic effect verification:

[0066] SiO2 particle size 20nm < 70nm (free path of air molecules at 1000℃) → inhibits convective heat transfer;

[0067] Particle size of light-blocking agent / wavelength = 2.8μm / 4μm = 0.7 times → radiation reflectivity 92%.

[0068] Fiber reinforcement calculation: =9μm≥4* * =4*0.05533*0.05=0.0107μm (valid) → Fiber breakage rate after compression is 0.3%.

[0069] like Figure 3As shown, it is lightweight and heat-resistant: density 280kg / m³, thermal conductivity 0.017W / m·k at 25℃, thermal conductivity 0.025W / m·k at 1000℃ (more than 40% lower than traditional ceramic fiberboard (≥0.050)); linear shrinkage rate of 2.0% at 1000℃ / 12h.

[0070] Example 2: Raw materials and proportions.

[0071] Vaporized SiO2: HS-200, 70%.

[0072] Gas phase Al2O3: Aluna-100, 8%.

[0073] Light-blocking agent: Yixing Guwang zirconium silicate, D50=2.0μm, 15%.

[0074] Reinforcing fiber: 3M Nextel ceramic fiber, 7μm in diameter, tensile strength 1500MPa, 7%.

[0075] Technical verification:

[0076] Light-shielding agent / wavelength ratio = 2.0μm / 3.0μm = 0.67 times → radiation reflectivity 93%.

[0077] Fiber reinforcement calculation: =7μm>0.0107μm (valid);

[0078] Component ratio optimized; compressive strength 1.5 MPa (25% higher than implementation 1).

[0079] Example 3: Raw materials and proportions.

[0080] Vaporized SiO2: HS-200 (amorphous), 80%;

[0081] Gas phase Al2O3: 0%;

[0082] Light-blocking agent: Silicon carbide GCW2.8, 15%;

[0083] Reinforcing fiber: Aluminosilicate fiber, 5μm in diameter, tensile strength 1000MPa, 5%.

[0084] Process adjustments:

[0085] Stirring blade 1: Linear velocity 9.5m / s (≤10m / s): Upper dispersion layer 11: 4 radial flat blades; Middle fiber mixed layer 12: 3 50° folding blades; Lower anti-deposition layer 13: 1 frame blade.

[0086] Verification: Calculation of reinforcing fibers;

[0087] =5μm≥4* * =0.020μm (valid) → fiber breakage rate 0.8%.

[0088] Even without Al2O3, it still meets the following performance requirements: thermal conductivity of 0.028 W / m·K at 1000℃ and shrinkage rate of 2.2% (close to the upper limit of 2.0%).

[0089] Example 4: Process-Specific Validation:

[0090] Folding blade propeller optimization: pitch angle 42° (range 45±5°).

[0091] The blade spacing is 18cm (0.6 times the blade diameter of 30cm).

[0092] Shaping process: After pressing, mechanically grind to a thickness tolerance of ±0.1mm.

[0093] Results: Surface flatness ≤0.1mm (conventional process ≤0.5mm); thermal stress cracking rate 0% (conventional process 12%).

[0094] Example 5: Boundary Parameter Verification:

[0095] Feeding interval: Al2O3→SiO2 interval 2 min (lower limit); SiO2→opaque agent interval 7 min (upper limit).

[0096] Pressing parameters: 50 tons hydraulic press (lower limit), pressing speed 30mm / s (upper limit).

[0097] Performance: Density 290 kg / m³ (upper limit); linear shrinkage rate 1.9% (meets ≤2.0%); verify the feasibility of the technical solution under process limits.

[0098] Comparative Example 1: Vapor phase SiO2 particle size 150nm (>70nm).

[0099] Results: Thermal conductivity at 1000℃ is 0.045 W / m·K (>0.038);

[0100] Proof: SiO2 particle size <70nm is crucial for suppressing convective heat transfer.

[0101] Comparative Example 2: Opacifier particle size 0.8 μm (<1.5 μm).

[0102] Result: Radiation reflectance 68% (<90%).

[0103] Proof: A light-blocking agent needs to be 1.5-6.0 μm thick to effectively reflect infrared radiation.

[0104] In summary: Examples 1-5 and comparative examples demonstrate that:

[0105] Synergistic effect of components: The particle size of gas-phase SiO2 <70nm reduces convective heat transfer by 60%; the radiation reflectivity is >90% when the particle size / wavelength of the opaque agent is 0.6 times; the fiber strength formula ensures that the breakage rate during the pressing process is <1%.

[0106] Technological advantages: The three-layer blade reduces density deviation by 67% compared to traditional dual-blade propellers; vacuum aluminum foil wrapping extends lifespan by 3 times at 1200℃;

[0107] Note: In the formula for verifying reinforcing fibers:

[0108] (μm)≥4* *

[0109] Since the actual fiber diameter (4-15μm) is much larger than the calculated result (0.01-0.05μm), this condition is naturally satisfied.

[0110] Finally, the following points should be noted: First, in the description of this application, it should be noted that, unless otherwise specified and limited, the terms "installation", "connection", and "linkage" should be interpreted broadly, and can be mechanical or electrical connections, or internal connections between two components, or direct connections. "Up", "down", "left", "right", etc. are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may change.

[0111] Secondly: The accompanying drawings of the embodiments disclosed in this invention only involve the structures involved in the embodiments disclosed in this invention. Other structures can refer to the general design. In the absence of conflict, the same embodiment and different embodiments of this invention can be combined with each other.

[0112] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-temperature resistant, lightweight nanoporous thermal insulation board, characterized in that, It consists of the following components: Nanoscale fumed silica: particle size 5–100 nm, mass percentage 60%–90%; Nanoscale fumed alumina: particle size 10–300 nm, mass percentage 0%–25%; Micron-sized opacifiers: silicon carbide powder and / or zirconium silicate powder, with a median particle size D50 of 1.5–6.0 μm and a mass percentage of 10%–35%; Reinforcing fibers: 4–15 μm in diameter, 2%–10% by mass; The components achieve the following functions through synergistic effects: Suppressing convective heat transfer in ambient air at 1000℃ and normal pressure; Reflects 2–5 μm infrared radiation heat; Maintain the integrity of the fiber structure during the pressing process; The synergistic effect is achieved through the following technical solutions: The particle size of the fumed silica is smaller than the mean free path of gas molecules in atmospheric air at 1000°C. The particle size of the light-blocking agent is 0.3–1.2 times the infrared wavelength; The diameter of the reinforcing fiber satisfies: ;in To enhance fiber diameter, the unit is μm. Fumed silica has a compressive strength of 50–100 MPa. To enhance the tensile strength of the fiber to 1000–2000 MPa, The average particle size of the fumed silica is 20–200 nm.

2. The ultra-high temperature resistant lightweight nanoporous insulation board according to claim 1, characterized in that, The ratio of the particle size of the light-blocking agent to the infrared wavelength is 0.5–0.8 times.

3. The ultra-high temperature resistant lightweight nanoporous insulation board according to claim 1, characterized in that, In the relationship between the diameters of the reinforcing fibers, Take 80MPa, Take 1500MPa, Taking 50nm, the calculation is as follows .

4. The ultra-high temperature resistant lightweight nanoporous insulation board according to claim 1, characterized in that, The fumed silica is in the form of amorphous nanoparticles.

5. The ultra-high temperature resistant lightweight nanoporous insulation board according to claim 1, characterized in that, The surface of the insulation board is covered with a vacuum aluminum foil layer, and the composition meets the following requirements: 65%–75% by mass of fumed silica, 8%–12% by mass of fumed alumina, 13%–18% by mass of light-blocking agent, and 5%–10% by mass of reinforcing fiber.

6. A method for preparing the insulation board according to any one of claims 1-5, characterized in that, Specifically, the following steps are included: S1. Add and stir the materials in the following order: fumed alumina → fumed silica → opaque agent, with an interval of 2–7 minutes between additions. S2. Add reinforcing fiber and continue stirring for 5–20 minutes; S3. Fill the mixture into the mold and press it into shape using a 50–400 ton hydraulic press at a pressing speed of 3–30 mm / s.

7. The method for preparing an insulation board according to claim 6, characterized in that, The stirring in steps S1 to S2 uses a combined impeller (1), which includes: Upper dispersible layer (11): radially arranged flat paddles used to disperse nano-agglomerates; Middle blended fiber layer (12): 30°–60° angled folding paddle for gently blending in reinforcing fibers; Bottom anti-deposition layer (13): Anchor or frame paddle, used to eliminate dead zone deposition; The blade (1) has a diameter of 20–50 cm, is covered with a silicone layer, rotates at 300–800 rpm and has a tip linear velocity ≤10 m / s.

8. The method for preparing an insulation board according to claim 7, characterized in that, The pitch angle of the blade of the middle fiber-mixed layer (12) is 45±5°, and the spacing between adjacent blades (1) is 0.6–1.0 times the blade diameter.

9. A method for preparing an insulation board according to claim 6, characterized in that, The pressing process employs a purely physical exhaust process.

10. A method for preparing an insulation board according to claim 6, characterized in that, After pressing and molding, the shape is adjusted.